Nutritional characteristics of grains fed to Canada Geese - Joyner, David E; Jacobson, Bruce N; Arthur, Robert D (Wildfowl, 1987)
Corn, milo, and wheat kernels were fed to penned Canada Geese during winter and spring to define seasonal coefficients of utilisation for grains. Corn and wheat showed a minor decrease in percent digestibility from winter to spring, whereas the digestibility of milo increased somewhat. Corn, which was preferred by geese over the other two grains, exceeded wheat in apparent metabolisable energy, produced the lowest digestible crude protein, and was intermediate in relative nitrogen retention. Wheat produced the lowest apparent metabolisable energy, but was highest in digestible crude protein and relative nitrogen retention. Milo equalled corn in apparent metabolisable energy, was intermediate in digestible crude protein, and lowest in relative nitrogen retention. The results suggest that as an emergency energy supply, corn and milo are equally suitable and both superior to wheat. As a crop, however, none of the three is entirely satisfactory if supplied alone.